Quality of life associated with immunosuppressant treatment adherence in liver transplant recipients: A cross-sectional study - Shafiekhani, Mojtaba; Shahabinezhad, Farbod; Tavakoli, Zahra; Tarakmeh, Tahereh; Haem, Elham; Sari, Negar; Nasirabadi, Shohreh; Dehghani, Masoud (Frontiers in Pharmacology, 2023)
Purpose: Transplanted organ survival after solid organ transplantation highly correlates with the adherence levels of the patients to their immunosuppressive drugs. On the other hand, one of the main goals of liver transplantation is to increase the overall quality of life (QOL) for the patient. This study is aimed to analyze the relationship between adherence and QOL in adult liver transplant recipients of the biggest liver transplant center in Asia. Methods: All of the included patients were older than 18 years and at least 6 months had passed from their liver transplantation. The adherence level was measured with BAASIS method and the QOL was assessed by SF-36 questionnaire in real-time interviews. The relationship between adherence and different aspects of QOL in addition to qualitative and quantitative influential factors on these two outcomes was calculated with statistical analysis. Results: Among the 122 included patients, 41% of the were categorized in the non-adherent group. The most important reasons for non-adherence in these patients included forgetfulness (62%), lack of medication (12%), financial problems for drug supply (9%), and side effects (2%). According to the results of the multivariate linear regression model, rejection was the only influential factor in the occurrence of non-adherence among patients (OR = 8.226 CI (1.404-48.196)). The overall mean QOL score of patients was reported 51.09 ± 21.86. The lowest is given to social functioning, while mental health has achieved the highest score. The mean QOL scores in different dimensions in patients with adherence were higher than non-adherents, which was only significant in mental health (p-value = 0.01). Additionally, in total scores related to Physical Composite Score (PSC) and Mental Composite Score (MCS), the mean MSC scores in adherent patients were significantly higher than non-adherent patients (p-value: 0.02). Although adherent patients have an overall greater QOL, the only meaningful effect on QOL total score was from income level. Conclusion: The overall QoL score has been in all parameters higher in the adherent group compared with non-adherent patients. The difference in QoL was most meaningfully significant in mental composite score among other parameters of QoL.